THE USE OF HEDGES AND BOOSTERS AS RHETORICAL DEVICES IN THE CONSTRUCTION OF SPEECHES - Farida Hidayati; Ruswan Dallyono (Masyarakat Linguistik Indonesia, 2015)
The present study is a pragmatic analysis of the use of hedges and boosters in the speeches of three ministers on the government’s policy of raising fuel prices during the second tenure administration of Susilo Bamband Yudhoyono (SBY). This study explores the distributions of hedges and boosters in the speeches and the pragmatic functions of those hedges and boosters. Data were obtained from three speeches delivered by Hatta Radjasa (HR), Jero Wacik (JW) and Armida Alisjahbana (AA). The theoretical framework of this study was based on Hyland’s (1998a) and Hyland’s (1998b) theories of hedging for categorizing the types of hedges and boosters and pragmatic functions. This study indicates that both hedges and boosters were used by two politicians: HR and AA with different distributions. This study confirms Hyland’s (1998a) and (1998b) findings that hedges and boosters are used for mitigating and strengthening the truth values of propositions.